2019
DOI: 10.1186/s13052-019-0757-0
|View full text |Cite
|
Sign up to set email alerts
|

Does virtual reality reduce pain in pediatric patients? A systematic review

Abstract: Virtual Reality (VR) as a tool for pain reduction is the research topic of several clinical trial for Randomized Controlled Trials despite its wide use in the daily clinical practice for non- pharmacological reduction of pain in some countries. At present, there are no published reviews of VR-efficacy of pain reduction in pediatric patients. That is why we made a systematic review of the efficacy of VR as a tool for pain reduction in children and adolescents. Electronic databases and gray literature published … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
41
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(45 citation statements)
references
References 13 publications
2
41
0
2
Order By: Relevance
“…Moreover, few studies have applied VR tools for pediatric chronic pain [12]. In a recent review of VR studies in pediatric pain (PubMed 2000-2017), there were only 4 that focused on VR for chronic pain, compared to 94 that focused on VR for coping with medical procedures and acute pain [13].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, few studies have applied VR tools for pediatric chronic pain [12]. In a recent review of VR studies in pediatric pain (PubMed 2000-2017), there were only 4 that focused on VR for chronic pain, compared to 94 that focused on VR for coping with medical procedures and acute pain [13].…”
Section: Introductionmentioning
confidence: 99%
“…Previous reviews have indicated the potential of VR in pediatrics (e.g., Eijlers et al, 2019a;Iannicelli et al, 2019;Georgescu et al, 2020). However, nearly half of the studies included in the present review were published in 2019 and 2020.…”
Section: Objectivesmentioning
confidence: 97%
“…In terms of clinical application, VR has also been investigated as a therapeutic tool, in particular for treating phobias, social disorder, and pain. Iannicelli et al [ 18 ] analysed the efficacy of VR as an instrument for pain reduction in children and adolescents. Although there are a few publications in this field, VR seems to be effective for non-pharmacological pain reduction.…”
Section: Critical Care 1- Dental Trauma; 2- Painmentioning
confidence: 99%